Intraocular Silicone Oil Masquerading as Terson Syndrome - Navid Elmi Sadr; Bijan Samavat; Payam Mehrian; Alireza Hedayatfar (Case Reports in Ophthalmological Medicine)
Introduction. Terson syndrome is described as intraocular hemorrhage in association with any type of intracranial hemorrhage and is associated with higher mortality rate and vision loss. Intraocular hemorrhage in Terson syndrome may be diagnosed using computed tomography but there are false positive results. Silicone oil which is widely used for internal tamponade of complicated retinal detachments has high attenuation on computed tomography and hyperintensity on T1-weighted magnetic resonance imaging that can mimic intraocular hemorrhage. This report shows that silicone oil is another origin of false positive results in interpreting CT findings for detecting Terson syndrome. Case Report. A 71-year-old diabetic woman presented with loss of consciousness. Brain computed tomography revealed right cerebellar hemorrhage and ventricular hemorrhage and hyperdensity in vitreous cavity of the left eye that was initially interpreted as vitreous hemorrhage. Terson syndrome was the initial diagnosis but ophthalmoscopic examination and brain MRI showed that the left eye had silicone oil tamponade. Conclusion. Without knowing the history of previous vitreoretinal surgery, CT scan findings of intraocular silicone oil may be interpreted as vitreous hemorrhage. In patients with concomitant intracranial hemorrhage, it can masquerade as Terson syndrome.